Efeitos do óleo da semente de neem (Azadirachta indica A. Juss) nos ovócitos e glândulas salivares de carrapatos Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) - Remedio, Rafael Neodini [UNESP] (2014)
Rhipicephalus sanguineus ticks have attracted, in recent years, the attention of researchers as well as public health managers, since they have become major urban pests, transmitters of diseases to humans and dogs. For this reason, the search for formulations with acaricide action has been constant concern of veterinary pharmaceutical industries. However, the vast majority of products currently commercialized exhibits high toxicity to the hosts of these ectoparasites and to the environment, even inducing resistance in ticks. Alternative control methods such as the use of plant extracts, for example, have become increasingly interesting, since they have reduced costs and low toxicity. In this sense, Azadirachta indica (neem) species stands out, as its leaf and seed extracts have recognized repellent, insecticide and acaricide potential. Thus, this study aimed to evaluate the morphological alterations resulting from the action of neem in the ovary and salivary glands of semi-engorged R. sanguineus female ticks, subjected to the topical application of the oil extracted from neem seeds, at concentrations of 20, 40 and 60%, using 10% aqueous ethanol as solvent. The organs were collected and fixed, and analyzed by means of techniques in conventional light microscopy, confocal laser scanning microscopy and transmission electron microscopy. In general, the methodology proposed in this work allowed the simulation of a topical treatment of the infested animals, making the results closer to a practical application in field. In both analyzed organs, neem oil clearly demonstrated a dose-dependent effect. Oocytes and glandular acini of R. sanguineus ticks exhibited similar morphological changes, such as evident signs of cytoplasmic disorganization, cellular vacuolation, nuclear or nucleolar irregularities, dilation of mitochondrial cristae, as well as dilation in rough endoplasmic reticulum lumen. These facts show that, regardless of the organ, neem ...